2012
DOI: 10.1093/jac/dks359
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NVB302 versus vancomycin activity in an in vitro human gut model of Clostridium difficile infection

Abstract: Both NVB302 and vancomycin were effective in treating simulated CDI in an in vitro gut model. C. difficile spore recrudescence was not observed following successful treatment with either NVB302 or vancomycin. NVB302 displayed non-inferiority to vancomycin in the treatment of simulated CDI, and had less deleterious effects against B. fragilis group. NVB302 warrants further clinical investigation as a potentially novel antimicrobial agent for the treatment of CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 28 publications
0
56
1
Order By: Relevance
“…It is highly selective for C. difficile versus normal gut flora, which may diminish the chance for recurrent infections. NVB302 displayed noninferiority to vancomycin in the treatment of simulated C. difficile infection in an in vitro human gut model (253). Novacta recently completed a phase 1 clinical trial in healthy volunteers, and NVB302 was found to be safe and well tolerated, with negligible systemic absorption of the drug and high concentrations recovered in the feces.…”
Section: Lff571mentioning
confidence: 99%
“…It is highly selective for C. difficile versus normal gut flora, which may diminish the chance for recurrent infections. NVB302 displayed noninferiority to vancomycin in the treatment of simulated C. difficile infection in an in vitro human gut model (253). Novacta recently completed a phase 1 clinical trial in healthy volunteers, and NVB302 was found to be safe and well tolerated, with negligible systemic absorption of the drug and high concentrations recovered in the feces.…”
Section: Lff571mentioning
confidence: 99%
“…Some promising candidates have been undergoing preclinical trials, like mutacin 1140 (MU1140) for dental and oral care, microbisporicin (NAI-107) for controlling severe infections caused by multidrugresistant Gram-positive pathogens, and lacticin 3147 for the treat-ment of systemic S. aureus infections (10)(11)(12). In addition, NVB302 (an actagardine derivative) and Moli1901 (duramycin) have completed phase I and phase II clinical trials for the treatment of Clostridium difficile infections (13) and cystic fibrosis (14,15). Hence, exploring novel and potent lantibiotics for clinical application has become a major interest with a promising future.…”
mentioning
confidence: 99%
“…Crowther et al conducted a recent study investigating the efficacy of NVB302 compared to vancomycin in treating CDI employing an in vitro gut model. 86 The gut microbiota count as well as C. difficile viable counts and spores were enumerated following NVB302 and vancomycin administration and a decrease in viable C. difficile counts with vancomycin and NVB302 administration was noted. NVB302 performed better than vancomycin as cytotoxin levels were undetectable 7 d subsequent to NVB302 administration, compared to undetectable cytotoxin levels 5 d after vancomycin instillation.…”
Section: Actagardine and Nvb302mentioning
confidence: 99%